New foods: a case study of Portuguese “Serra da Estrela” cheese incorporated with chestnuts flowers - Carocho, Márcio (2015)
The “Serra da Estrela” is the most well-known Portuguese cheese, made from ewe’s milk for centuries, granted a Protected Designation of Origin (PDO) in 1996 by the European Union. To this date, not many studies have been carried out regarding the nutritional profile of this cheese. Chestnut flowers are usually leftovers of the nut harvest, and, being a very interesting flower in terms of antioxidants and antimicrobials, the incorporation of this by-product into the cheese may be of interest to both the farmers and food industry. For one, it could become an additional source of income for the agrarian, while being a natural antimicrobial and antioxidant, reducing the need of chemical conservatives, which is a growing concern among the food industries. Herein, nutritional profiles of three samples are reported: control cheese, cheese incorporated with lyophilized powdered flower and cheese incorporated with lyophilized flower decoction. The main differences regarding macronutrients composition and energetic value will be assessed, along with an overview of individual free sugars, tocopherols and fatty acids.